EMPIRICAL ASSESSMENT ON ADOPTION OF PROGESTERONE IMPREGNATED VAGINAL SPONGE BY THE DAIRY FARMERS OF TAMIL NADU - S. Karthikeyan; N. Narmatha; V. Uma; K. Sivakumar; G. Kumaresan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was undertaken to ascertain the present status of adoption of progesterone impregnated vaginal sponge like complete adoption, partial adoption, discontinuance and rejection and its perceived attributes like relative advantage, compatibility, complexity, observability and trialability using the schedule developed for this purpose and its economic impact. Partial budgeting was done to assess the economic impact of adopting progesterone impregnated vaginal sponge. Farmers were aware about the progesterone impregnated vaginal sponge through the constituent units of TANUVAS like veterinary colleges, KVKs and VUTRCs (84%); veterinary officers (47%); extension workers (46%); friends and relatives (34%). Majority (80%) of the respondents reported to have completely adopted the innovation for treating infertility while the remaining (20%) had discontinued it. Majority of the dairy farmers (78%) were in the medium level of adoption behaviour about the innovation followed by low (12%) and high (10%) level. Most of the dairy farmers perceived that progesterone impregnated vaginal sponge was cheaper in price, exorbitantly profitable, time saving, situationally and culturally feasible, physically compatible, trialable, adoptable and the results are observable. Partial budgeting analysis revealed that net income of the dairy farmers was increased by Rs. 28,041.90 per dairy animal due to the adoption of progesterone impregnated vaginal sponge in their infertile dairy animals. The present status of adoption of innovation by farmers was positively correlated with land holding and dairy animal possession and change in net income at 1% level, while their adoption behaviour was positively correlated with education and change in net income at 1% level and with land holding and extension agency at 5% level of significance.